Catalyst‐Controlled Multicomponent Aziridination of Chiral Aldehydes. Issue 11 (27th January 2017) - Mukherjee, Munmun; Zhou, Yubai; Dai, Yijing; Gupta, AniL K.; Pulgam, V. Reddy; Staples, Richard J.; Wulff, William D.
Abstract: A highly diastereoselective and enantioselective method for the multicomponent aziridination of chiral aldehydes has been developed with BOROX catalysts of the VANOL( 3, 3′‐diphenyl‐2, 2′‐bi‐1‐naphthol) and VAPOL (2, 2′‐diphenyl‐(4‐biphenanthrol)) ligands. Very high to perfect catalyst control is observed with most all substrates examined including aldehydes with chiral centers in the α‐ and β‐positions. High catalyst control was also observed for a number of chiral heterocyclic aldehydes allowing for the preparation of epoxy aziridines, bis(aziridines) and ethylene diaziridines. Application of this reaction in the synthesis of β 3 ‐homo‐d ‐alloisoleucine and β 3 ‐homo‐l ‐isoleucine is reported. Abstract : This way or that —a strict binary decision is all that is required. The stereochemical outcome of the aziridination reaction of chiral aldehydes can be simply selected by the choice of the catalyst antipode—an outcome that for most substrates is independent of the nature and the stereochemistry of substituents at either the β‐ or α‐positions of the aldehyde.